Serum ferritin as an indicator of iron status: what do we need to know? - Daru, Jahnavi; Colman, Katherine; Stanworth, Simon J; De La Salle, Barbara; Wood, Erica M; Pasricha, Sant-Rayn (The American journal of clinical nutrition, 2017)
Determination of iron status in pregnancy and in young children is essential for both clinical and public health practice. Clinical diagnosis of iron deficiency (ID) through sampling of bone marrow to identify the absence of body iron stores is impractical in most cases. Serum ferritin (SF) concentrations are the most commonly deployed indicator for determining ID, and low SF concentrations reflect a state of iron depletion. However, there is considerable variation in SF cutoffs recommended by different expert groups to diagnose ID. Moreover, the cutoffs used in different clinical laboratories are heterogeneous. There are few studies of diagnostic test accuracy to establish the sensitivity and specificity of SF compared with key gold standards (such as absent bone marrow iron stores, increased intestinal iron absorption, and hemoglobin response to SF) among noninflamed, outpatient populations. The limited data available suggest the commonly recommended SF cutoff of <15 μg/L is a specific but not sensitive cutoff, although evidence is limited. Data from women during pregnancy or from young children are especially uncommon. Most data are from studies conducted >30 y ago, do not reflect ethnic or geographic diversity, and were performed in an era for which laboratory methods no longer reflect present practice. Future studies to define the appropriate SF cutoffs are urgently needed and would also provide an opportunity to compare this indicator with other established and emerging iron indexes. In addition, future work would benefit from a focus on elucidating cutoffs and indexes relevant to iron adequacy.